Safety, tolerability and immunogenicity of the ExPEC4V (JNJ-63871860) vaccine for prevention of invasive extraintestinal pathogenic Escherichia coli disease: A phase 1, randomized, double-blind, placebo-controlled study in healthy Japanese participants. Issue 9 (2nd September 2018) - Inoue, Megumi; Ogawa, Tetsuro; Tamura, Hiroshi; Hagiwara, Yosuke; Saito, Yuki; Abbanat, Darren; van den Dobbelsteen, Germie; Hermans, Peter; Thoelen, Stefan; Poolman, Jan; Ibarra de Palacios, Patricia
ABSTRACT: This Phase 1, randomized, double-blind, placebo-controlled study was conducted to evaluate the safety, tolerability and immunogenicity of different doses of ExPEC4V conjugate vaccine (4-16µg Polysaccharide [PS]/serotype) in healthy Japanese participants, stratified into younger (≥20 to <50 years) or older age groups (≥50 years). Within each age group, participants were randomized to a single vaccination with 1 of 3 dose levels of ExPEC4V (4, 8 and 16 µg PS/serotype) or placebo. Safety and tolerability were the primary objectives; immunogenicity was secondary. Of the 48 participants, 47 (98%) completed; one (2%) in the placebo group discontinued. A total of 48% participants had ≥1 AE (younger group: n = 13 [54%]; older group: n = 10 [41.7%]). Solicited and unsolicited AEs were reported in 44% and 8% participants, respectively in the combined ExPEC4V groups. Pain/tenderness (n = 11 [31%]) and redness (n = 9 [25%]) were the most frequently reported solicited local AEs, whereas fatigue (n = 4 [11%]), headache (n = 4 [11%]), muscle pain (n = 2 [6%]), and malaise (n = 5 [14%]) were the most common solicited systemic AEs in the combined ExPEC4V group. No serious AEs, deaths, or discontinuation due to AEs were reported. All doses were immunogenic with an increase in IgG (ELISA) geometric mean titers of at least 5-fold from baseline to Days 15 and 30 for all serotypes. Of participants vaccinated with ExPEC4V, 75% - 100% demonstrated an ELISA titer increase of ≥2-fold. Strong correlation observed between ELISA and OPK. ExPEC4V was well tolerated and elicited an immunogenic response at all dose levels (up to 16 µg PS/serotype) in healthy Japanese participants.